Local Labor Market Effects of the 2002 Bush Steel Tariffs - James Lake; Ding Liu (Center for Economic Studies and ifo Institute (CESifo), 2022)
President Bush imposed safeguard tariffs on steel in early 2002. Using US input-output tables and a generalized difference-in-difference methodology, we analyze the local labor market employment effects of these tariffs depending on the local labor market's reliance on steel as an input and as part of local production. We find the tariffs did not boost local steel employment but substantially depressed local employment in steel-consuming industries for many years after Bush removed the tariffs. These large and persistent negative effects were concentrated in local labor markets that had low human capital or were strongly specialized in steel-consuming industries.
Keywords: F13; F14; F16; 330; Bush steel tariffs; safeguard tariffs; local labor markets; intermediate inputs; downstream; steel-consuming